2019
DOI: 10.1111/boc.201800075
|View full text |Cite
|
Sign up to set email alerts
|

Dying under pressure: cellular characterisation and in vivo functions of cell death induced by compaction

Abstract: Cells and tissues are exposed to multiple mechanical stresses during development, tissue homoeostasis and diseases. While we start to have an extensive understanding of the influence of mechanics on cell differentiation and proliferation, how excessive mechanical stresses can also lead to cell death and may be associated with pathologies has been much less explored so far. Recently, the development of new perturbative approaches allowing modulation of pressure and deformation of tissues has demonstrated that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 104 publications
(183 reference statements)
1
23
0
Order By: Relevance
“…Enveloped biologics such as viruses, vaccines and cells are usually the main components sensitive to mechanical destruction. Valon et al studied the possible effects of mechanical stresses on various types of cells, and reported that shear stresses and compaction may lead to apoptosis and cell death [73]. Choi et al also found that hyperosmotic pressure can destroy virus integrity in an acidic environment [32].…”
Section: Challenges Associated With Oral Deliverymentioning
confidence: 99%
“…Enveloped biologics such as viruses, vaccines and cells are usually the main components sensitive to mechanical destruction. Valon et al studied the possible effects of mechanical stresses on various types of cells, and reported that shear stresses and compaction may lead to apoptosis and cell death [73]. Choi et al also found that hyperosmotic pressure can destroy virus integrity in an acidic environment [32].…”
Section: Challenges Associated With Oral Deliverymentioning
confidence: 99%
“…This mechanical competition was described as a new and alternative mode of cell competition and may be relevant in a wide range of genetic and tissue backgrounds. Recent reviews have already discussed the process of mechanical-based competition [59][60][61] and the role of mechanical forces in death induction [62]. We will therefore give a rather brief overview here of the concept of mechanical competition by describing first how cell deformation can trigger cell elimination, then focusing on two alternative modes of compaction-driven elimination.…”
Section: Regulation Of Cell Death By Mechanical Inputs and Mechanical Cell Competitionmentioning
confidence: 99%
“…This data was consistent with the T D as aforementioned. It has been evidenced that cell deformability is associated with cytotoxicity and cell death, and the late stage of cell deformation can lead to a loss of the cell membrane and ultimately cellular disruption and death 43 , 44 . On the other hand, the protein-free AU-Siriraj formula did not induce the cell death, consistent with our previous study demonstrating that this AU formula is quite physiologic 1 .…”
Section: Discussionmentioning
confidence: 99%